2022
DOI: 10.12681/psyhps.30840
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction among psychology students: the role of resilience and perceived economic hardship

Abstract: The present study aimed to investigate internet addiction among psychology students, as well as the role of resilience and perceived economic hardship in the manifestation of the phenomenon. The study involved 252 students (233 women, 19 men) of Aristotle University of Thessaloniki. They completed a self-report questionnaire, which included a short version of a scale on resilience (The Connor-Davidson Resilience Scale - CD-RISC), a scale on perceived economic hardship (Economic Hardship Questionnaire), and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…For example, the COVID-19 pandemic has had a widespread impact on the level of digital engagement worldwide. This has drawn attention to the potential risk of IA regardless of demographic factors [ [1] , [2] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the COVID-19 pandemic has had a widespread impact on the level of digital engagement worldwide. This has drawn attention to the potential risk of IA regardless of demographic factors [ [1] , [2] ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has worsened this situation, resulting in students using the internet excessively, beyond normal or even addictive levels. This is characterized by patterns such as uncontrolled internet use and neglect of social life [ 1 ]. The global implementation of containment and quarantine measures to mitigate the spread of COVID-19 [ 2 ] and restrictions across various sectors have had wide-ranging and uncertain impacts [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the descriptive findings showed that the participating students expressed a relatively high sense of loneliness and a moderate sense of resilience, reflecting young adults’ negative emotions since the outbreak of the COVID-19 pandemic (Ernst et al 2022 ; Groarke et al 2020 ; Hwang et al 2020 ; Rosenberg 2020 ; Touloupis 2021 ; Touloupis and Athanasiades 2022 ; Vinkers et al 2020 ; Zhang et al 2022 ). It is likely that the significant and sudden changes in university students’ daily routine during the last two years of the COVID-19 pandemic have caused a collectively more vulnerable emotional state among youth.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that strengthening sense of resilience of young adults who feel lonely during crisis periods, such as the COVID-19 pandemic, could act as a protective filter against the development of an intense and possibly less safe pattern of Facebook use. This necessity is even more pronounced considering the relatively low sense of resilience among the participating students as well as the generally vulnerable emotional state (high sense of loneliness and low sense of resilience) of young adults during and in the aftermath of the COVID-19 pandemic (Ernst et al 2022;Groarke et al 2020;Hwang et al 2020;Rosenberg 2020;Touloupis 2021;Touloupis and Athanasiades 2022;Zhang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…was studied. Psychological resilience is one of the important factors that can predict smartphone / internet addiction [16,17]. The mediating effect between resilience and smartphone / internet addiction was researched in relation to life satisfaction [18], teacher-student relationship [16], or depression [19], but the relationship towards factors such as academic achievement is understudied.…”
Section: Review Of Current Evidence On This Study Topicmentioning
confidence: 99%